A System of Differential Set-Valued Variational Inequalities in Finite Dimensional Spaces. (4th February 2014) - Li, Wei; Wang, Xing; Huang, Nan-Jing
Abstract : A system of differential set-valued variational inequalities is introduced and studied in finite dimensional Euclidean spaces. An existence theorem of weak solutions for the system of differential set-valued variational inequalities in the sense of Carathéodory is proved under some suitable conditions. Furthermore, a convergence result on Euler time-dependent procedure for solving the system of differential set-valued variational inequalities is also given.